Efektifitas Samsat J’bret (Samsat Jawa Barat Ngabret) oleh Unit Regident Satuan Lantas di Wilayah Polres Karawang Dalam Melayani Registrasi Kendaraan Bermotor - Engelina Yusuf (Indonesian Journal of Police Studies, 2020)
In today's modern era of the era that is the era of the Revolution 4.0 industrial Revolution that collaborates with cyber technology with automation technology. Where using the technology of the community can more easily access any information through the Internet network, in the current digital era police also have to do the improvement in its service system. There is no problem in the problems used is 1) How Services Office Samsat j'bret mechanism in public service by the unit regident units to be in the Karawang?, 2) How is the effectiveness of the program quality of service services Office Samsat J'bret in improving public services?, 3) How to do regident unit so that Karawang in the Program effective Services Office Samsat J'bret in the region, Karawang?. Based on the problems taken then the author performs observations to get information on the research to be taken by the author. In this research the authors use management theory is the theory of effectiveness, management theory that is planning (planning), organization (organizing), implementation (actuating), supervision (controling) and some concepts that are the concept of effectiveness, Concept Services Office Samsat J'bret, Concept regident, the concept of public service. Data collection techniques using interviews, observations, document studies, data validity and data analysis techniques used using data reduction, and data presentation The results of this research show that J'bret Services Office Samsat program has not been implemented effectively. In this program there is also a data leakage between identity card and Vehicle Registration Certificate different name and still many people who do not know about this J'bret Services Office Samsat program. There are many people who prefer to come to the office directly because they do not know how to operate the program and sometimes there are obstacles in the form of Internet network. So the need of the police and Bapenda cooperate to perform the improvement in the application and also continue to socialize more people who know about this application and the benefits that can also be gained from the facilities provided through this program.